Discover a wealth of knowledge at Westonci.ca, where experts provide answers to your most pressing questions. Get detailed and accurate answers to your questions from a community of experts on our comprehensive Q&A platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
Certainly! Let's solve the problem step-by-step to determine how many zeroes the polynomial [tex]\((x-3)^2 - 4\)[/tex] has and find what those zeroes are.
### Step 1: Write the Polynomial in Standard Form
First, we start with the given polynomial:
[tex]\[ (x-3)^2 - 4 \][/tex]
### Step 2: Simplify the Polynomial
Expand the expression:
[tex]\[ (x-3)^2 - 4 = (x-3)(x-3) - 4 \][/tex]
[tex]\[ = x^2 - 6x + 9 - 4 \][/tex]
[tex]\[ = x^2 - 6x + 5 \][/tex]
### Step 3: Set the Polynomial Equal to Zero
To find the zeroes, we need to solve:
[tex]\[ x^2 - 6x + 5 = 0 \][/tex]
### Step 4: Solve the Quadratic Equation
We can factorize the quadratic equation:
[tex]\[ x^2 - 6x + 5 = (x-1)(x-5) = 0 \][/tex]
### Step 5: Set Each Factor to Zero and Solve for x
Solving for [tex]\(x\)[/tex] from each factor:
[tex]\[ x - 1 = 0 \quad \Rightarrow \quad x = 1 \][/tex]
[tex]\[ x - 5 = 0 \quad \Rightarrow \quad x = 5 \][/tex]
### Step 6: Conclusion
Thus, the polynomial [tex]\((x-3)^2 - 4\)[/tex] has 2 zeroes, and they are:
[tex]\[ x = 1 \quad \text{and} \quad x = 5 \][/tex]
Therefore, the polynomial [tex]\((x-3)^2 - 4\)[/tex] has two zeroes, which are [tex]\(1\)[/tex] and [tex]\(5\)[/tex].
### Step 1: Write the Polynomial in Standard Form
First, we start with the given polynomial:
[tex]\[ (x-3)^2 - 4 \][/tex]
### Step 2: Simplify the Polynomial
Expand the expression:
[tex]\[ (x-3)^2 - 4 = (x-3)(x-3) - 4 \][/tex]
[tex]\[ = x^2 - 6x + 9 - 4 \][/tex]
[tex]\[ = x^2 - 6x + 5 \][/tex]
### Step 3: Set the Polynomial Equal to Zero
To find the zeroes, we need to solve:
[tex]\[ x^2 - 6x + 5 = 0 \][/tex]
### Step 4: Solve the Quadratic Equation
We can factorize the quadratic equation:
[tex]\[ x^2 - 6x + 5 = (x-1)(x-5) = 0 \][/tex]
### Step 5: Set Each Factor to Zero and Solve for x
Solving for [tex]\(x\)[/tex] from each factor:
[tex]\[ x - 1 = 0 \quad \Rightarrow \quad x = 1 \][/tex]
[tex]\[ x - 5 = 0 \quad \Rightarrow \quad x = 5 \][/tex]
### Step 6: Conclusion
Thus, the polynomial [tex]\((x-3)^2 - 4\)[/tex] has 2 zeroes, and they are:
[tex]\[ x = 1 \quad \text{and} \quad x = 5 \][/tex]
Therefore, the polynomial [tex]\((x-3)^2 - 4\)[/tex] has two zeroes, which are [tex]\(1\)[/tex] and [tex]\(5\)[/tex].
Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.